PENGARUH ARUS KAS OPERASI, TINGKAT UTANG, DAN OPINI AUDIT TERHADAP PERSISTENSI LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2013-2016 - Aini, Amira Qurrata; Zuraida, Zuraida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The study aims to determine the effect of operating cash flow, leverage, and audit opinions on earnings persistence. The population of this study is mining companies listed in Indonesian Stock Exchange in 2013-2016. The sample selected by purposive sampling method. The data used in this research is secondary data in the form of financial statement companies. Data analysis was performed using multiple linear regression statistical analysis. The results of this research show that operating cash flow, leverage, and audit opinions simultaneously influence earnings persistence. Partially operating cash flow and leverage significantly influence earnings persistence, whereas, audit opinions do not influence earning persistence.